2003
DOI: 10.4269/ajtmh.2003.68.624
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Optimal Test for Malaria Diagnosis Among Suspected Malaria Patients at the Rural Health Centers

Abstract: Abstract. The OptiMAL test detects both Plasmodium falciparum and P. vivax malaria infections. In this study, we evaluated the performance of the OptiMAL test at the Basic Health Units (BHUs) and the District Health Quarter (DHQ) Center in rural villages of Punjab, Pakistan that provide minimal health services. Two sets of blood specimens obtained from 930 suspected malaria patients attending these BHUs were tested at BHUs and the DHQ Center by microscopy and the OptiMAL test. At the BHUs, 231 (25%) of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 20 publications
3
27
0
4
Order By: Relevance
“…16 The results of present study indicated that 50 (20.16%) were infected with malaria and and the rest 198 (79.20%) were malaria negative out of total 248 blood samples. This matched the results of the study done by Iqbal et al 17 [2003] who obtained blood specimens from 930 suspected malaria patients attending BHU and found 231 [25%] to be positive.…”
Section: Discussion:-supporting
confidence: 78%
“…16 The results of present study indicated that 50 (20.16%) were infected with malaria and and the rest 198 (79.20%) were malaria negative out of total 248 blood samples. This matched the results of the study done by Iqbal et al 17 [2003] who obtained blood specimens from 930 suspected malaria patients attending BHU and found 231 [25%] to be positive.…”
Section: Discussion:-supporting
confidence: 78%
“…The OptiMAL test shows sensitivity similar to those reported for other dipsticks, such as ParaSight and ICT Malaria Pf/Pv, which ranged from 86-100 and 58-96%, respectively (3,20,(28)(29)(30)(31)(32)(33) Coleman et al (35) evaluated the efficacy of the ICT Malaria Pf/Pv in a large study of 559 asymptomatic patients from an endemic area of Thailand using conventional microscopy as the reference method, and found that the sensitivity for P. falciparum dropped from 100 to 23.3% when the parasitemia was below 500 trophozoites/µL. For P. vivax infections, the sensitivity dropped from 66.7% to 0 at parasitemia below 500 trophozoites/µL.…”
Section: Discussionmentioning
confidence: 70%
“…The adoption of RDT by community health workers could facilitate diagnosis in local malaria-endemic areas with limited health personnel and facilities (Harvey et al, 2008). However, the accuracy of a clinical diagnosis is dependent on the disease endemicity level, malaria season and the age group under consideration (Dicko et al, 2005;Mwangi et al, 2005), thus the discrepancies observed in RDT sensitivities in several observational studies (Grobusch et al, 2003;Iqbal et al, 2003;Fernando et al, 2004).…”
Section: Introductionmentioning
confidence: 99%